2017
DOI: 10.3390/e19030132
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between Conventional Multiscale Entropy and Modified Short-Time Multiscale Entropy of Photoplethysmographic Pulse Signals in Middle- and Old- Aged Individuals with or without Diabetes

Abstract: Abstract:Multiscale entropy (MSE) of physiological signals may reflect cardiovascular health in diabetes. The classic MSE (cMSE) algorithm requires more than 750 signals for the calculations. The modified short-time MSE (sMSE) may have inconsistent outcomes compared with the cMSE at large time scales and in a disease status. Therefore, we compared the cMSE of 1500 (cMSE 1500 ) consecutive and 1000 photoplethysmographic (PPG) pulse amplitudes with the sMSE of 500 PPG (sMSE 500 ) pulse amplitudes of bilateral fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the previously study, we used multiscale cross approximately entropy (MCAE) to analyze the PPG pulse amplitudes of bilateral index fingertip (left and right) in the middle-to-old individuals and revealed that the signal from the right finger was more challenging for analysis than the left finger [12]. Therefore, in this present study, we used only PPG pulse amplitude from the right finger.…”
Section: Discussion and Study Limitationsmentioning
confidence: 99%
“…In the previously study, we used multiscale cross approximately entropy (MCAE) to analyze the PPG pulse amplitudes of bilateral index fingertip (left and right) in the middle-to-old individuals and revealed that the signal from the right finger was more challenging for analysis than the left finger [12]. Therefore, in this present study, we used only PPG pulse amplitude from the right finger.…”
Section: Discussion and Study Limitationsmentioning
confidence: 99%
“…The authors of the study report that the MSE index for the dominant hand was significantly different between people with poorly and well-controlled diabetes, while the MSE index for the non-dominant hand allowed for the diagnosis of healthy people. In their conclusions, the authors suppose that the MSE of PPG pulse amplitudes can be used to assess microcirculation in people with type 2 diabetes [40].…”
Section: The Use Of Ppg In the Assessment Of Blood Circulation In Patmentioning
confidence: 97%
“…As other researchers have pointed out, also other data provided by PPG may be useful in assessing the vitality of the cardiovascular system in diabetics. Gen-Min Lin et al [40] in their research they analyzed Multiscale Entropy (MSE) of PPG pulse amplitudes. They carried out their study on a group of 80 volunteers (36 healthy, 22 with well-controlled diabetes HbA1c <8% and 22 with poorly controlled blood glucose HbA1c ≥ 8%), each performing 1500 resting pulses amplitudes of bilateral index fingers.…”
Section: The Use Of Ppg In the Assessment Of Blood Circulation In Patmentioning
confidence: 99%
“…Since our previous study showed similar MSE levels of 1500 PPG pulse amplitudes between right and left fingertip in both unaffected individuals and those with diabetes [20], the left fingertip MSE was to be the representative for the analysis. The results of sample entropy between scale factors 1 and 5 were defined as small scales, and those between scale factors 6 and 10 were defined as large scales.…”
Section: Mse Of Unilateral Fingertip Ppga Pulse Amplitudementioning
confidence: 99%